(untitled) (Journal for Studies in Humanities and Social Sciences, 2014)
The rapidly growing presence of old and new media in postcolonial Namibia, particularly from the decade after the turn of the Millennium, has signifi cance for cultural and lifestyle transformations in the country. Formerly entrenched social identities, shaped by restrictive colonialism and indigenous traditions, appear to be under pressure as shifts become apparent in the face of cultural globalisation. This article examines the characteristics of change from the perspective of young Windhoek adults’ experiences of Internet social networks. The research constitutes a cultural study that addresses the current knowledge gap regarding how the Internet is increasingly situated in youth identity and cultural lifestyle spaces. Social networks appear to be changing the cultural landscapes of Namibia, if the evidence is accepted, and youth are at the cutting edge of cultural transformations wrought by new media such as the Internet.